2018
DOI: 10.1007/978-3-319-78674-2
|View full text |Cite
|
Sign up to set email alerts
|

Dictionary Learning Algorithms and Applications

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(66 citation statements)
references
References 1 publication
0
66
0
Order By: Relevance
“…Our model is a good fit for online representation scenarios which is why we plan on investigating in the future its adaptation to online dictionary learning [25], where the dictionary is also updated with each new signal that is sparsely represented. Existing methods have shown that the dictionary update problem can be reduced to a simple rank-1 update D ← D + Γ ( [15], Chapter 5) and we are currently working on changing Γ in order to exploit the existing multi-parametric model of the existing dictionary.…”
Section: Discussionmentioning
confidence: 99%
“…Our model is a good fit for online representation scenarios which is why we plan on investigating in the future its adaptation to online dictionary learning [25], where the dictionary is also updated with each new signal that is sparsely represented. Existing methods have shown that the dictionary update problem can be reduced to a simple rank-1 update D ← D + Γ ( [15], Chapter 5) and we are currently working on changing Γ in order to exploit the existing multi-parametric model of the existing dictionary.…”
Section: Discussionmentioning
confidence: 99%
“…Dictionary learning [33] provides heuristics that approximate solutions to the following problem: given a dataset Y ∈ R n×N , a sparsity level s and the size of the dictionary S we want to create a dictionary D ∈ R n×S and the sparse representations X ∈ R S×N then solve…”
Section: The Proposed Dictionary Learning Algorithmsmentioning
confidence: 99%
“…If n ITC is much smaller than the current n, we decrease the size by δ − (this number is 5 in our experiments); if n ITC is only slightly smaller, than we decrease the size by one; finally, we interpret n ITC = n as a sign that the size needs to be increased and add δ + atoms to the dictionary (we take δ + = 5). There are several methods for generating new atoms [3] (Section 3.9); we choose the simplest: random atoms.…”
Section: Algorithmmentioning
confidence: 99%
“…Dictionary learning (DL) is now a mature field [1][2][3], with several efficient algorithms for solving the basic problem or its variants and with numerous applications in image processing (denoising and inpainting), classification, compressed sensing and others. The basic DL problem is: given N training signals gathered as the columns of the matrix Y ∈ R m×N and the sparsity level s, find the dictionary D ∈ R m×n by solving min…”
Section: Introductionmentioning
confidence: 99%